Indian newspaper reports, c1868-1942, from the British Library, London (Adam Matthew Publications Ltd., 2005)
Consists of weekly typewritten abstracts taken from a wide variety of Indian newspapers, with some extracts. Translated by an official translator. Each report is divided into the following sections: Foreign politics -- Home administration: Police. Working of the courts. Jails. Education. Local self-government and municipal administration. Questions affecting the land. Railways and communications, including canals and irrigation. General (including a wide range of topics) -- Legislative -- Native States -- Prospects of the crops and condition of the people -- Miscellaneous.